Analyzing the environmental impacts and potential health challenges resulting from artisanal gold mining in Shango area of Minna, North-Central, Nigeria - Adegbe Mamodu; Ile Theophilus Ojonimi; Simon Samchi Apollos; Orji-Chukwuma N Jacinta; Waziri H Salome; Abubakar Abduljalilu Enesi (Journal of Degraded and Mining Lands Management, 2018)
The environmental impact and potential health challenges resulting from artisanal mining in Shango area of Minna, North Central Nigeria was put into perspective. The methodology adopted for the research includes field work and laboratory analysis. Results of field observation reveal that mining activity resulted in physical environmental impact such as land degradation, destruction of vegetation, erosion of soils and degrading water quality. Results from the laboratory analyses show that soils are contaminated with elements such as Cu (27.7ppm), Cd (0.6 ppm), Hg (0.62 ppm) and Ag (0.35 ppm) and generally show high status when compared to published standard for upper continental crust. While, Zn (14.8ppm), Ni (7.17ppm), Mn (207ppm), Pb (0.58ppm), As (0.4ppm), Co (0.55ppm), Mo (0.16ppm), and Zr (129.8ppm) are rated low in line with the published standard; other determined elements such as Cr (37.8ppm), Fe (31.1ppm) and Au (0.2ppm) are high. These elements can easily be absorbed by plants and subsequently accumulate in their tissues. When such plants are eventually eaten by man, it may lead to different health problems such as slow growth rate, liver and kidney problem. High concentration of these elements in plant tissues may causes different problems.